Mitochondrial nucleoid morphology and respiratory function are altered in Drp1-deficient HeLa cells. (24th December 2019) - Ota, Azusa; Ishihara, Takaya; Ishihara, Naotada
Abstract: Mitochondria are dynamic organelles that frequently divide and fuse with each other. The dynamin-related GTPase protein Drp1 has a key role in mitochondrial fission. To analyse the physiological roles of Drp1 in cultured human cells, we analysed Drp1-deficient HeLa cells established by genome editing using CRISPR/Cas9. Under fluorescent microscopy, not only mitochondria were elongated but their DNA (mtDNA) nucleoids were extremely enlarged in bulb-like mitochondrial structures ('mito-bulbs') in the Drp1-deficient HeLa cells. We further found that respiratory activity, as measured by oxygen consumption rates, was severely repressed in Drp1-deficient HeLa cells and that this was reversible by the co-repression of mitochondrial fusion factors. Although mtDNA copy number was not affected, several respiratory subunits were repressed in Drp1-deficient HeLa cells. These results suggest that mitochondrial fission is required for the maintenance of active respiratory activity and the morphology of mtDNA nucleoids in human cells.